2018
DOI: 10.1177/0025802418790857
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in the assessment of paediatric traffic injuries and deaths

Abstract: Motor-vehicle collisions are the leading cause of unintentional injury and death in children in many parts of the world, including Europe, North America and Australia. The number of fatal collisions has decreased considerably in countries where safety measures such as child restraints, seat belts and air bags have been introduced, providing protection for children within vehicles, although it is recognised that there have been concomitant improvements in emergency responses and techniques, and in hospital trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…37 There is also a much higher rate of child pedestrian mortality and injury in countries of lower socioeconomic status, as children often work in stalls beside busy roads, in markets without safe or any footpaths, and even selling goods in and around idling vehicles at traffic lights. 38 Working can also significantly negatively impact upon social development if a child spends most of his or her time labouring instead of interacting with peers in communal play and learning how to socialize appropriately. Even adolescents who work may be affected, and it has been shown that teenagers who spend more than 20 hours per week working are at a higher risk of developing problematic social behaviour such as drug abuse and physical aggression.…”
Section: Effects Of Child Labourmentioning
confidence: 99%
See 1 more Smart Citation
“…37 There is also a much higher rate of child pedestrian mortality and injury in countries of lower socioeconomic status, as children often work in stalls beside busy roads, in markets without safe or any footpaths, and even selling goods in and around idling vehicles at traffic lights. 38 Working can also significantly negatively impact upon social development if a child spends most of his or her time labouring instead of interacting with peers in communal play and learning how to socialize appropriately. Even adolescents who work may be affected, and it has been shown that teenagers who spend more than 20 hours per week working are at a higher risk of developing problematic social behaviour such as drug abuse and physical aggression.…”
Section: Effects Of Child Labourmentioning
confidence: 99%
“…There is also a much higher rate of child pedestrian mortality and injury in countries of lower socioeconomic status, as children often work in stalls beside busy roads, in markets without safe or any footpaths, and even selling goods in and around idling vehicles at traffic lights. 38…”
Section: Effects Of Child Labourmentioning
confidence: 99%
“…For example, death rates in children from vehicle crashes/collisions are very high in countries with low socioeconomic status, where children often work beside busy roads and sometimes within traffic. 6 According to World Health Organization data, death rates from vehicles range from 45.1 per 100,000 population in Venezuela to 3.2 in San Marino. 5 In the present study accidents were the largest category of unnatural deaths, with 135 cases occurring over 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…The injury status of child occupants under correct and incorrect use of child seats was studied [ 18 ]. Three kinds of crash conditions were simulated and analyzed for the integrated safety seat, and the variable design parameters were optimized [ 19 ].…”
Section: Related Workmentioning
confidence: 99%